2019
DOI: 10.1002/ldr.3487
|View full text |Cite
|
Sign up to set email alerts
|

Changes in topsoil organic carbon from 1986 to 2010 in a mountainous plateau region in Southwest China

Abstract: The carbon cycle and underlying environmental drivers are not yet fully understood, and whether climate warming is inducing soil carbon loss remains controversial, largely due to limited evidence from large‐scale observations. With relatively less human disturbance, Yunnan Province, a typical mountainous plateau region in Southwest China, is a favorable place to evaluate environmental effects on soil organic carbon (SOC) dynamics. In this study, soil sampling of the upper 20‐cm soil layer was conducted at site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…However, as we hypothesized, we found that the size and direction of SOC changes seemed to be elevation-dependent, i.e., the SOC stock decreased significantly in mid-elevation zones, while it increased in high-elevation zones and varied less in low-elevation zones in the study area. Similar results were also demonstrated by Chen et al [2], who found that soils in the Yunnan province experienced intense carbon losses at 3000-3500 m while significant accumulation above 4500 m during the period of 1986-2015. In addition, Ding et al [51] found that soils of alpine grasslands of the Tibetan Plateau (>4000 m) were also characterized by significant carbon accumulation from the 2000s to the 2010s.…”
Section: Elevation-dependent Soc Dynamicssupporting
confidence: 89%
See 1 more Smart Citation
“…However, as we hypothesized, we found that the size and direction of SOC changes seemed to be elevation-dependent, i.e., the SOC stock decreased significantly in mid-elevation zones, while it increased in high-elevation zones and varied less in low-elevation zones in the study area. Similar results were also demonstrated by Chen et al [2], who found that soils in the Yunnan province experienced intense carbon losses at 3000-3500 m while significant accumulation above 4500 m during the period of 1986-2015. In addition, Ding et al [51] found that soils of alpine grasslands of the Tibetan Plateau (>4000 m) were also characterized by significant carbon accumulation from the 2000s to the 2010s.…”
Section: Elevation-dependent Soc Dynamicssupporting
confidence: 89%
“…In alpine regions, elevation-dependent warming probably results in a higher temperature increase over higher elevation regions. Consequently, the patterns and dynamics of soil organic carbon (SOC) in alpine ecosystems are being markedly reshaped [1][2][3]. In addition, a large amount of SOC is stored in alpine ecosystems due to the cold and humid climate conditions, thus even small changes in temperature and precipitation could greatly affect SOC stock dynamics [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous cropland studies were mainly focused on evaluating the impacts of long‐term fertilization on SOC (Chen et al, 2020; Mustafa et al, 2020; Tong et al, 2014) and TN stocks (Han et al, 2020) in the topsoil layers (0–30 cm), except for one trial conducted by Samson et al (2021), who quantified long‐ and short‐term influences of mineral fertilizers and organic manure on C and N stocks up to 60‐cm depth of a soil profile. Nonetheless, the impacts of long‐term manure and mineral fertilizers on SOC and TN stocks in the complete soil profile (0–100 cm) remain neglected in the past, which in the current study demonstrates the uniqueness of this endeavour.…”
Section: Introductionmentioning
confidence: 99%
“…The farmland ecosystem is susceptible to anthropogenic factors, and soil nutrients and aggregate characteristics are invariably affected by tillage methods and straw returning (Wang, Wang et al., 2019). Soil disturbances caused by different tillage measures lead to SOC loss (Chen et al., 2020), with considerable adverse effects on soil aggregate stability and carbon content linked to soil disturbance (Kabiri et al., 2015). By contrast, soil conservation tillage could be an effective way to resolve the issue of soil degradation and to increase the soil SOC contents that resulted in the effective sequestration of 372 million tons of CO 2 per year (Vermeulen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%